PENGARUH PEMBERIAN KOMPOS SERASAH TERHADAP PERTUMBUHAN BIBIT STUM MATA TIDUR KARET PADA MEDIA GAMBUT - albertus ronald; Sopiana Sopiana; Venti Jatsiyah (Politeknik Negeri Ketapang, 2023)
The problem faced in rubber nurseries on a large scale is the limitation of fertile soil. An effort to overcome this problem is to utilize peat soil with rubber leaf litter compost treatment. The purpose of this study was to determine the effect of giving a dose of rubber leaf litter compost on the growth of sleeping eye stum rubber seeds and to determine the best dose of rubber leaf litter compost on the growth of sleeping eye stum rubber seedlings. The research was carried out in the experimental garden of Gg. Hj. Salbiah Delta Pawan District, Ketapang Regency, West Kalimantan from April to July 2021. The study used a single factor Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments used were K0 = 1000 g peat soil, K1 = 300 g rubber leaf litter compost + 700 g peat soil, K2 = 400 g rubber leaf litter compost + 600 g peat soil and K3 = 500 g rubber leaf litter compost + 500 g peat. The data obtained were analyzed statistically with Analysis of Variances (ANOVA) using the SAS application version 9.0. If it is significantly different, then it is continued with the Duncan Multiple Range Test (DMRT) further test at the 5% level. The results showed that the addition of rubber leaf litter had a significant effect on shoot height, stem diameter, number of umbrellas and root length. The dose of rubber leaf litter compost 500 g rubber litter compost + 500 g peat soil is the best treatment to increase the growth of sleeping eye stumps.